Electrophysiological Characteristics of the LQT2 Syndrome Mutation KCNH2-G572S and Regulation by Accessory Protein KCNE2 - Liu, Li; Tian, Jinwen; Lu, Caiyi; Chen, Xi; Fu, Yicheng; Xu, Bin; Zhu, Chao; Sun, Yanmei; Zhang, Yu; Zhao, Ying; Li, Yang (Frontiers in Physiology, 2016)
Mutations in hERG cause long QT syndrome type 2 which is characterized by a prolonged QT interval on electrocardiogram and predisposition to life-threatening ventricular tachyarrhythmia, syncope and sudden death. hERG-G572S induces trafficking defects of hERG channel protein from Golgi to the plasma membrane and results in a dominant negative suppression of hERG current density. As an accessory β subunit, KCNE2 promotes hERG migration from Golgi to cellular membrane. In this study, we investigated the rescue effect of KCNE2 in a G572S mutation of hERG. Transfection was performed into HEK293 cells. Patch clamp technique, western blotting analyses and confocal microscopic examination were used. Results showed that KCNE2 had a significantly enhanced effect on G572S mutation current. The increase of current was largest at KCNH2:KCNE2 of 1:3. Confocal images showed co-expressing G572S and KCNE2 could cause a substantial up-regulated membrane protein (155kDa) expression. Expression of membrane protein accumulated markedly with increasing ratio of KCNH2:KCNE2. G572S defective mutant could be restored by both KCNE2 and lower temperature (27℃), which suggested that the lower temperature could be the favorable circumstances for the rescue function of KCNE2. In this study, we successfully set up “the action potential” on the HEK 293 cells by genetically engineered to express Kir2.1, Nav1.5 and Kv11.1, wherein on reaching over an excitation threshold by current injection. The results suggested that KCNE2 could shorten action potential duration which was prolonged by G572S. These findings described electrophysiological characteristics of the LQT2 syndrome mutation KCNH2-G572S and regulation by accessory protein KCNE2, and provided a clue about LQT2 and relative rescue mechanism.